Analysis of off-farm work decisions among smallholder farm households in Burkina Faso. Issue 3 (3rd April 2019) - Gansonré, Soumaila
ABSTRACT: This article investigates off-farm work decisions by smallholder farm households. Using data on 1, 101 households from Burkina Faso, it demonstrates that in addition to the usual household socio-demographic characteristics, remittances, access to information and beneficiary of specific training affect off-farm work decisions, as well as rainfall factors and idiosyncratic health shocks. Community characteristics such as accessibility and number of inhabitants are also key factors. While suggesting that off-farm work is less likely to be undertaken for accumulation purposes, these results have important policy implications. In particular, policy measures should consider each segment as a separate entity.